2019
DOI: 10.3390/ijerph17010226
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Mechanisms in the Treatment of Wastewater Due to Interaction of Benzaldehyde and Iron Slag Byproduct

Abstract: Iron slag is a byproduct generated in huge quantities from recycled remnants of iron and steel factories; therefore, the possibility of using this waste in the removal of benzaldehyde from contaminated water offers an excellent topic in sustainability field. Results reveal that the removal efficiency was equal to 85% for the interaction of slag and water contaminated with benzaldehyde at the best operational conditions of 0.3 g/100 mL, 6, 180 min, and 250 rpm for the sorbent dosage, initial pH, agitation time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In addition, the results confirmed that the presence of lemna minor would increase the reduction of cephalexin by adopting suitable initial concentrations since lemna minor will provide the required environment for phytoremediation growth within the root zone and other parts of lemna minor (Kouki et al, 2009). Light-harvesting and energy transfer in the plant, the photosystem is responsible for the active core (Baker, 2008;Faisal et al, 2020c). In plants, radical superoxide (O −2 ) is naturally generated during photosynthesis in chloroplasts, especially when plants develop under conditions of environmental stress.…”
Section: Cephalexin Initial Concentration Effectmentioning
confidence: 53%
“…In addition, the results confirmed that the presence of lemna minor would increase the reduction of cephalexin by adopting suitable initial concentrations since lemna minor will provide the required environment for phytoremediation growth within the root zone and other parts of lemna minor (Kouki et al, 2009). Light-harvesting and energy transfer in the plant, the photosystem is responsible for the active core (Baker, 2008;Faisal et al, 2020c). In plants, radical superoxide (O −2 ) is naturally generated during photosynthesis in chloroplasts, especially when plants develop under conditions of environmental stress.…”
Section: Cephalexin Initial Concentration Effectmentioning
confidence: 53%
“…Each value of q e in this figure represents the average of three readings; however, the standard deviation for these readings must be calculated and plotted in the same figure as “error bars”. It is clear that the two isotherms are well described by the sorption data, namely the “coefficient of determination, R 2 ” had the highest value and the “sum of squared errors, SSE” had the lowest value [ 54 , 55 ]. The (1/ n ) is smaller than unity; so, there is favorable adsorption for SO 4 2− ions onto the prepared sorbent.…”
Section: Resultsmentioning
confidence: 99%
“…These sorption measurements are fitted with the Langmuir and Freundlich isotherm models that represented by Eqs. 2 and 3 respectively [1,7,8,16,18]:…”
Section: Preparation Of Coated Sand and Equilibrium Experimentsmentioning
confidence: 99%
“…Langmuir and Freundlich's models are fitted with sorption data for the interaction of cadmium and copper ions with CSIO for q e (mg/g) with C e (mg/L) as shown in Figure 3. The fitted constants with statistical measures have been calculated from nonlinear regression -Microsoft Excel (2016) [1,7,8,16,18] as listed in Table 1. This figure in conjugation with a determination coefficient (R 2 ) and the sum of squared errors (SSE) elucidated that the model of Langmuir is more representative of sorption data.…”
Section: Sorption Isothermsmentioning
confidence: 99%